Impact of Slow Deep Breathing on Pain in Head Injury Patients: A Systematics Review - Kogoya, Neger; Mulyanto, Joko (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2025)
Head injury is a global health problem that often resulted from traffic accidents, and has a serious impact on brain and nervous system function. One of the main symptoms of head injury is intense pain, which often affects patients' quality of life. Although pain medications are widely used, non-pharmacological interventions such as the Slow Deep Breathing (SDB) technique have been proposed as an effective alternative to reduce pain in head injury patients. This study was aimed to evaluate the impact of SDB on pain reduction in patients with head injury. This systematic review was conducted using the PRISMA method with journal searches in several databases such as Google Scholar and PubMed. The search focused on studies published between 2020 to 2024. Screened articles had to meet the inclusion criteria involving observational studies on SDB in head injury pain. In this systematic review, information was collected by highlighting key elements, including the population group, type of intervention measures, outcomes observed, and methodological approach chosen. the result of the 425 journals identified, 95 articles were screened, and 4 journals met the criteria for further discussion. The results of the four studies showed that the SDB technique significantly reduced pain intensity in head injury patients. SDB helped lower heart rate, blood pressure, and improve blood oxygenation, all of which contributed to pain reduction. Slow Deep Breathing technique was shown to be effective as a non-pharmacological treatment for managing pain in head injury patients. Despite some limitations in sample size and study design, consistent results support the use of SDB as a complementary therapy in pain management. Future research is needed to inform the maximum therapeutic activity of SDB and explore the potential for combination with other therapies